The Putative SLC Transporters Mfsd5 and Mfsd11 Are Abundantly Expressed in the Mouse Brain and Have a Potential Role in Energy Homeostasis - Perland, Emelie (PLoS One, 2016)
BACKGROUND: Solute carriers (SLCs) are membrane bound transporters responsible for the movement of soluble molecules such as amino acids, ions, nucleotides, neurotransmitters and oligopeptides over cellular membranes. At present, there are 395 SLCs identified in humans, where about 40% are still uncharacterized with unknown expression and/or function(s). Here we have studied two uncharacterized atypical SLCs that belong to the Major Facilitator Superfamily Pfam clan, Major facilitator superfamily domain 5 (MFSD5) and Major facilitator superfamily domain 11 (MFSD11). We provide fundamental information about the histology in mice as well as data supporting their disposition to regulate expression levels to keep the energy homeostasis. RESULTS: In mice subjected to starvation or high-fat diet, the mRNA expression of Mfsd5 was significantly down-regulated (P<0.001) in food regulatory brain areas whereas Mfsd11 was significantly up-regulated in mice subjected to either starvation (P<0.01) or high-fat diet (P<0.001). qRT-PCR analysis on wild type tissues demonstrated that both Mfsd5 and Mfsd11 have a wide central and peripheral mRNA distribution, and immunohistochemistry was utilized to display the abundant protein expression in the mouse embryo and the adult mouse brain. Both proteins are expressed in excitatory and inhibitory neurons, but not in astrocytes. CONCLUSIONS: Mfsd5 and Mfsd11 are both affected by altered energy homeostasis, suggesting plausible involvement in the energy regulation. Moreover, the first histological mapping of MFSD5 and MFSD11 shows ubiquitous expression in the periphery and the central nervous system of mice, where the proteins are expressed in excitatory and inhibitory mouse brain neurons.